Business Formalization to Strengthen the Commercial Negotiation of Independent Waste Recyclers - Pérez-Arboleda, Pedro Antonio; Contreras-Julián, Rosa Mabel; Mendoza-Banda, Tania Yasely; Chanamé-Díaz, Gino; Luján Johnson, Gladys Lola; Aparicio-Ballena, Jorge Alberto (Journal of Ecohumanism, 2024)
In Latin America, cities are experiencing serious environmental problems due to rapid growth that exceeds their capacity for governance. At this juncture, the independent informal recycler is the workforce dedicated to the collection of recyclable inorganic solid waste that contributes to the effectiveness of municipal management. Thus, the objective was to determine the influence of business formalization and commercial negotiation from the perspective of these people. It was a basic, non-experimental, quantitative, causal correlational study. Three hundred waste pickers were surveyed using two validated and reliable questionnaires. The data was analyzed by ordinal logistic regression. It was determined that business formalization had a significant influence on commercial negotiation; however, there are aspects related to productivity and the application/compliance with legality that should be analyzed from a governmental management perspective, in order to provide better conditions to guarantee the sustainability of this activity within the communes. The role of municipal managers should be oriented on two main fronts: technical-legal and strategic management with a sustainable vision within the framework of the state modernization plan and the need to maintain the ecological balance that will sustain human survival in the future.